2007
DOI: 10.1210/en.2006-0681
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B-Cell Transcription Factor 1 and Steroidogenic Factor 1 Synergistically Regulate Adrenocortical Growth and Steroidogenesis

Abstract: A variety of transcription factors including Wilms tumor gene (Wt-1), steroidogenic factor 1 (Sf-1), dosage-sensitive sex reversal, adrenal hypoplasia congenita on the X-chromosome, Gene 1 (Dax-1), and pre-B-cell transcription factor 1 (Pbx1) have been defined as necessary for regular adrenocortical development. However, the role of Pbx1 for adrenal growth and function in the adult organism together with the molecular relationship between Pbx1 and these other transcription factors have not been characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Protein extraction and immunoblots were performed as described (18). Phosphorylated Smad1/5/8 (1:500), phosphorylated AKT (pAKT; 1:5,000), total AKT (1:5,000, all from Cell Signaling Technology, Inc.), and h-actin antibody (1:5000; Sigma-Aldrich Corp.) were used as primary antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Protein extraction and immunoblots were performed as described (18). Phosphorylated Smad1/5/8 (1:500), phosphorylated AKT (pAKT; 1:5,000), total AKT (1:5,000, all from Cell Signaling Technology, Inc.), and h-actin antibody (1:5000; Sigma-Aldrich Corp.) were used as primary antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Pbx1 expression was decreased in Sf-1 haploinsufficient animals. This indicated that Sf-1 could stimulate Pbx1 expression in the adult adrenal [59]. Whether a similar feedforward loop exists in the foetal adrenal is still unknown.…”
Section: Fetal Adrenal Enhancer (Fade)mentioning
confidence: 93%
“…This apparent contradiction can be explained by the fact that sucrose-treated animals display significantly lower Mc2r expression levels in the adrenal cortex (l'Allemand et al 1996, Lichtenauer et al 2007, Waddell et al 2010. The origin and significance of this finding deserve further investigation.…”
Section: Weeks Of Treatmentmentioning
confidence: 95%